KOPUMPSA rises to 211th place in Malaysia’s Best Cooperatives 2025 - Muhamad, Mat Noor (UMPSA, 2025)
KUANTAN, 7 August 2025 – Koperasi Universiti Malaysia Pahang Al-Sultan Abdullah Berhad (KOPUMPSA) has once again made the university community proud by climbing to 211th place in the 2025 ranking of Malaysia’s Best Cooperatives.